2017
DOI: 10.1007/s11356-017-8504-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of urban soils contaminated with trace metals using Noccaea caerulescens: comparing non-metallicolous populations to the metallicolous ‘Ganges’ in field trials

Abstract: Urban soil contamination with trace metals is a major obstacle to the development of urban agriculture as crops grown in urban gardens are prone to accumulate trace metals up to toxic levels for human consumption. Phytoextraction is considered as a potentially cost-effective alternative to conventional methods such as excavation. Field trials of phytoextraction with Noccaea caerulescens were conducted on urban soils contaminated with Cd, Cu, Pb, and Zn (respectively around 2, 150-200, 400-500, and 400-700 μg g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…For example, nonmetalliferous accessions of N. caerulescens are often characterized by a lower biomass compared to accessions from metal-contaminated soils (Escarré et al 2013). Comparing a large number of N. caerulescens accessions, it was observed that calamine accessions produce the greatest shoot biomass (Sterckeman et al 2017), as also shown in our experiment. Haines (2002) reported that a higher plant biomass was obtained when roots of N. caerulescens were foraging for Zn; in our results, this effect was not observed for Ni, as no biomass variations were recorded in correspondence with higher Ni supply, Ni shoot uptake or root proliferation in Ni-enriched areas (Tables 1 and 2 ;Figs.…”
Section: Plant Biomasssupporting
confidence: 90%
See 3 more Smart Citations
“…For example, nonmetalliferous accessions of N. caerulescens are often characterized by a lower biomass compared to accessions from metal-contaminated soils (Escarré et al 2013). Comparing a large number of N. caerulescens accessions, it was observed that calamine accessions produce the greatest shoot biomass (Sterckeman et al 2017), as also shown in our experiment. Haines (2002) reported that a higher plant biomass was obtained when roots of N. caerulescens were foraging for Zn; in our results, this effect was not observed for Ni, as no biomass variations were recorded in correspondence with higher Ni supply, Ni shoot uptake or root proliferation in Ni-enriched areas (Tables 1 and 2 ;Figs.…”
Section: Plant Biomasssupporting
confidence: 90%
“…3 ), even if it was not statistically significant for the Plombieres accession growing in the garnierite treatment. Variability in growth rates between the two accessions of N. caerulescens can be related to the natural morphological and physiological differences in accessions of this species (Ingrouille and Smirnoff 1986;Sterckeman et al 2017). For example, nonmetalliferous accessions of N. caerulescens are often characterized by a lower biomass compared to accessions from metal-contaminated soils (Escarré et al 2013).…”
Section: Plant Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of different pollution levels, appropriate strategies should be used to maximize the phytoremediation effect. Phytoextraction, which uses hyperaccumulator plants to remove heavy metals from soil, is suggested for remediation of slightly and moderately contaminated soils [11,12], while phytostabilization is thought to be practical for remediation of multi-metal highly contaminated soils [13,14].…”
Section: Introductionmentioning
confidence: 99%